2022
DOI: 10.2147/rru.s365598
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Caesalpinia bonduc Seed Extracts Ameliorates Testosterone-Induced Benign Prostatic Hyperplasia (BPH) in Male Wistar Rats

Abstract: Introduction Benign prostatic hyperplasia (BPH) is a major chronic disease affecting men, and the therapeutic agents currently used to manage it have significant side effects. As a result, an alternative medicine with improved therapeutic properties with no side effects is desperately needed. The current investigation aims to study whether the Caesalpinia bonduc seed extracts (ethanolic-A, hydroalcoholic-B, and aqueous-C) have inhibitory potential on testosterone propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…The collected seeds were washed with tap water to remove debris and then dried in a hot air oven at 40°C until constant weight. Once fully dried, the seeds were grounded by mechanical milling until a fine powder was obtained ( Sasidharan et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
“…The collected seeds were washed with tap water to remove debris and then dried in a hot air oven at 40°C until constant weight. Once fully dried, the seeds were grounded by mechanical milling until a fine powder was obtained ( Sasidharan et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
“…The three dried extracts [Ethanolic extract of C. bonduc seeds (EECS), Hydroalcoholic extract of C. bonduc seeds (HECS) & Aqueous extract of C. bonduc seeds (AECS)] thus obtained were stored at 4°C for future studies. ( Sasidharan et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…[15] The shell includes protein and amino acids, with a quantity ranging from 7.430 to 25.346%. Sasidharan et al (2022) have shown that seeds exhibit anti-diabetic characteristics, which are especially significant in the setting of type 2 diabetes. Elevated blood glucose levels define this metabolic disorder due to decreased insulin production or responsiveness.…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%
“…Elevated blood glucose levels define this metabolic disorder due to decreased insulin production or responsiveness. [16] In the contemporary pharmaceutical landscape, evaluating leaf and stem bark extracts for their analgesic properties, along with the isolated (Roxb. ), holds immense significance.…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%